(untitled) (Itinera, 2023)
Dante Alighieri’s Divine Comedy is rich in visual and imaginative suggestions, capable of intertwining in total harmony with words and triplets in alternating rhyme, giving life to a unique and fascinating work. Over the centuries, the “divine poem” has inspired generations of authors and artists, who have re-proposed Dante’s journey into the afterlife through different languages ​​and expressive codes, first of all representative art. Above all, the visual and artistic translations of Dante’s work have influenced many writers and cartoonists who, starting from lithographs and ancient tables - think of the Divine Comedy illustrated by Gustave Doré in the second half of the nineteenth century - have developed their own transposition of the poem, in the wake of innovation and experimentation. In fact, the tradition of Dante in comics has its roots in the early twentieth century and knows an extraordinary development throughout the century both in Italy and abroad. From Disney’s Mickey’s Inferno to Marcello Toninelli’s Divine Comedy, from Go Nagai’s monumental manga work to Hunt Emerson’s Dante’s Inferno, Dante’s triplets capture the attention of comic book fans all over the world, presenting themselves not only as an interesting reading for pleasure, but also as an effective didactic-pedagogical tool for students. In fact, the comic is not only synonymous with entertainment, but also a means capable of adapting the complex content of the Divine Comedy to an audience of primary school pupils, from which it is possible to start a profitable didactic planning, which sees protagonists and “cartoonists” the children themselves.